2006
DOI: 10.1177/000331970605700201
|View full text |Cite
|
Sign up to set email alerts
|

Venoruton® vs Daflon®: Evaluation of Effects on Quality of Life in Chronic Venous Insufficiency

Abstract: The aim of this independent study was to investigate differences in efficacy between oxerutins (Venoruton) and 500 mg micronized diosmin + hesperidin (D+H) (Daflon) in patients with chronic venous insufficiency (CVI), evaluating venous-related quality of life (Ve-QOL). A first group of 90 patients with severe venous hypertension (CVI, ankle swelling) was randomized to treatment with oxerutins or D+H. The oxerutins group received oral oxerutins (2 g/day); the D+H group received 3 (500 mg) tablets daily every 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
2
41
0
1
Order By: Relevance
“…Diosmin is a flavonoid and an active ingredient in Daflon-500 that may improve venous tone, microvascular permeability, lymphatic activity, and microcirculatory nutritive flow (Le Devehat et al, 1997). Rutosides enhance endothelial function in patients with CVI (Cesarone et al, 2006). Flavonoids may affect the endothelium and leukocytes and reduce edema and inflammation.…”
Section: Matrix Metalloproteinases In Varicose Veinsmentioning
confidence: 99%
“…Diosmin is a flavonoid and an active ingredient in Daflon-500 that may improve venous tone, microvascular permeability, lymphatic activity, and microcirculatory nutritive flow (Le Devehat et al, 1997). Rutosides enhance endothelial function in patients with CVI (Cesarone et al, 2006). Flavonoids may affect the endothelium and leukocytes and reduce edema and inflammation.…”
Section: Matrix Metalloproteinases In Varicose Veinsmentioning
confidence: 99%
“…In Europe, it is prescribed for treatment of venous insufficiency while in the US, it is marketed as a food supplement [60,61]. A study in rat liver perfusate showed that diosmin was mainly excreted in the bile as a glucuronide conjugate [62].…”
Section: Diosminmentioning
confidence: 99%
“…Following an application from Omikron Italia S.r.l, submitted pursuant to Article 13(5) of Regulation (EC) No 1924No /2006 via the Competent Authority of Italy, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to a combination of diosmin, troxerutin and hesperidin and maintenance of normal venous tone.…”
Section: Discussionmentioning
confidence: 99%
“…EFSA is requested to evaluate the scientific data submitted by the applicant in accordance with Article 16(3) of Regulation (EC) No 1924No /2006. On the basis of that evaluation, EFSA will issue an opinion on the scientific substantiation of a health claim related to a combination of diosmin, troxerutin and hesperidin and maintenance of normal venous tone.…”
Section: Terms Of Referencementioning
confidence: 99%